2017
DOI: 10.1111/dar.12534
|View full text |Cite
|
Sign up to set email alerts
|

Health conditions and motivations for marijuana use among young adult medical marijuana patients and non‐patient marijuana users

Abstract: Patients were significantly more likely to report a range of health conditions and motivations associated with medical use than non-patients. A great majority of patients reported obtaining a medical marijuana recommendation for health problems in accordance with the California law. [Lankenau SE, Ataiants J,Mohanty S, Schrager S, Iverson E, Wong CF.Health conditions and motivations for marijuana use among young adultmedical marijuana patients and non-patient marijuana users. Drug Alcohol Rev 2017;00:000-000].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Regarding differences between medical and non-medical users, a notably higher proportion of medical users were female, heterosexual, and reported a chronic health condition than non-medical users. Overall, the qualitative sample (n=40) approximated the larger sample (n=210) on several demographic characteristics, i.e., age, race/ethnicity, employment status, while the qualitative sample had a higher proportion of women, lesbian, gay, bisexual, or transgender, and college-educated participants (Lankenau et al, 2017b). Additionally, the qualitative sample reported similar days of marijuana use and ERQ scores compared to the larger sample but had a greater proportion of young adults reporting a chronic health condition.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Regarding differences between medical and non-medical users, a notably higher proportion of medical users were female, heterosexual, and reported a chronic health condition than non-medical users. Overall, the qualitative sample (n=40) approximated the larger sample (n=210) on several demographic characteristics, i.e., age, race/ethnicity, employment status, while the qualitative sample had a higher proportion of women, lesbian, gay, bisexual, or transgender, and college-educated participants (Lankenau et al, 2017b). Additionally, the qualitative sample reported similar days of marijuana use and ERQ scores compared to the larger sample but had a greater proportion of young adults reporting a chronic health condition.…”
Section: Resultsmentioning
confidence: 95%
“…For some in this group, their own definitions of legitimate medical use, e.g., treatment for cancer, epilepsy, did not match their own patterns of use, e.g., “taking the edge off,” so that they did not self-identify as a medical user. Furthermore, if protection or legal access was the primary reason for obtaining a medical marijuana recommendation (Lankenau et al, 2017b), some kind of new discovery of medical use needed to occur for the participant to regard him or herself as a medicinal user.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 However, medical cannabis patients are 1.6 times more likely to report pain conditions, 1.4 times more likely to report neurological conditions, and twice as likely to report mental health issues than young adults who use cannabis recreationally. 25 With respect to characteristics of use, Tucker et al reported that among 671 adolescents aged 13-19 using cannabis in California, having a medical cannabis card was associated with greater quantity and frequency of use, as well as greater risk of cannabis-associated problems including: driving under the influence of cannabis (DUIC), missing school or work, and lower performance in school. 24 Those with medical cannabis cards were also more likely to report having felt the need to cut down or quit cannabis in the last three months.…”
Section: Prevalence and Characteristics Of Medical Cannabis Use Amongmentioning
confidence: 99%
“…Data utilised in the present analysis were collected within the Cannabis, Health & Young Adults (CHAYA) project [26,27], which collected four waves of quantitative data.…”
Section: Data Sourcementioning
confidence: 99%